Erythropoietin mediates re-programming of endotoxin-tolerant macrophages through PI3K/AKT signaling and protects mice against secondary infection - Zhang, Xue; He, Dan; Jia, Jialin; Liang, Feihong; Mei, Jie; Li, Wenhua; Liu, Tingting; Wang, Zhiyu; Liu, Yu; Zhang, Fengxue; Zhang, Zhiren; Luo, Bangwei (Frontiers in Immunology, 2022)
Initial LPS exposure leads to a hypo-responsive state by macrophages to a secondary stimulation of LPS, known as endotoxin tolerance. However, recent findings show that functions of endotoxin-tolerant macrophages are not completely suppressed, whereas they undergo a functional re-programming process with up-regulation of a panel of molecules leading to enhanced protective functions including anti-microbial and tissue-remodeling activities. However, the underlying molecular mechanisms are still elusive. Erythropoietin (EPO), a glycoprotein regulated by hypoxia-inducible factor-1α (HIF-1α), exerts anti-inflammatory and tissue-protective activities. Nevertheless, the potential effects of EPO on functional re-programming of endotoxin-tolerant macrophages have not been investigated yet. Here, we found that initial LPS exposure led to up-regulation of HIF-1α/EPO in macrophages, and that EPO enhanced tolerance in tolerized macrophages and mice as demonstrated by suppressed proinflammatory genes such as Il1b, Il6 and Tnfa after secondary LPS stimulation. Moreover, we showed that EPO improved host protective genes in endotoxin-tolerant macrophages and mice, such as the anti-bacteria genes coding for Cathelicidin-related antimicrobial peptide (Cnlp) and macrophage receptor with collagenous structure (Marco), and the tissue-repairing gene vascular endothelial growth factor-C (Vegfc). Therefore, our findings indicate that EPO mediates the functional re-programming of endotoxin-tolerant macrophages. Mechanistically, we found that PI3K/AKT signaling contributed to EPO-mediated re-programming through up-regulation of Irak3 and Wdr5 expression. Specifically, IRAK3 was responsible for inhibiting proinflammatory genes Il1b, Il6 and Tnfa in tolerized macrophages after LPS rechallenge, while WDR5 contributed to up-regulation of host beneficial genes including Cnlp, Marco and Vegfc. In a septic model of mice, EPO pretreatment significantly promoted endotoxin-tolerant re-programming, alleviated lung injury, enhanced bacterial clearance and decreased mortality in LPS-tolerized mice after secondary infection of Escherichia coli. Collectively, our results reveal a novel role for EPO in mediating functional re-programming of endotoxin-tolerant macrophages, thus targeting EPO appears to be a new therapeutic option in sepsis and other inflammatory disorders.